A Retrospective Study on Mandibular Reconstruction Following Excision of Canine Acanthomatous Ameloblastoma - Tsugawa, Anson J.; Arzi, Boaz; Vapniarsky, Natalia; Verstraete, Frank J. M. (Frontiers in Veterinary Science, 2022)
The successful excision of a locally invasive tumor such as canine acanthomatous ameloblastoma (CAA) typically results in a mandibular contour-derforming, critical-size defect that alters the jaw kinematics and may affect the patient’s quality of life. In this case series, we describe our experience using the regenerative approach of a titanium locking plate and compression resistant matrix (CRM) infused with rhBMP2 for the immediate or delayed reconstruction following mandibulectomy for the excision of mandibular CAA in 11 dogs. Surgical planning included computed tomography (CT), with and without contrast, in all cases, and 3D-printed models in 4 cases. Tumor-free surgical margins were achieved in all dogs. Clinical and diagnostic imaging follow-up (mean, 23.1 months) were performed in-person (11 cases) and with CT/CBCT in most cases, with standard radiography (3 cases) and telemedicine being utilized in 5 cases. At 2 weeks postoperatively hard tissue was palpable at the defect. Follow-up imaging at one month postoperatively revealed evidence of bridging new bone with a heterogeneous appearance, that remodeled over 3-6 months to bone of a similar size, shape and trabecular pattern as native bone. Histological evaluation of regenerated bone was available in two cases, and was supportive of our clinical and imaging findings of normal remodeled bone. Clinically, all dogs returned to a normal lifestyle, rapidly resumed eating and drinking, and exhibited normal occlusion. Complications included wound dehiscence in one dog and self-limiting exuberant bone formation in two dogs. Tumor regrowth, failure of the implant or fracture of the regenerated bone was not observed. We conclude that mandibular reconstruction using a regenerative approach is safe, feasible and results in restoration of mandibular contour in dogs following segmental and bilateral rostral mandibulectomy for benign but invasive oral tumors such as CAA.